The American Public's Energy Choice - Ansolabehere, Stephen and Konisky, David M. (Daedalus, 2012)
Public opinion about energy can be understood in a unified framework. First, people evaluate key attributes of energy sources, particularly a fuel's cost and environmental harms. Americans, for example, view coal as relatively inexpensive but harmful, natural gas as less harmful but more expensive, and wind as inexpensive and not harmful. Second, people place different weights on the economic and environmental attributes associated with energy production, which helps explain why some fuels are more popular than others. Americans' attitudes toward energy are driven more by beliefs about environmental harms than by perceived economic costs. In addition, attitudes about energy sources are largely unrelated to views about global warming. These findings suggest that a politically palatable way to reduce greenhouse gas emissions is through regulation of traditional pollutants associated with fossil fuels, rather than a wholly new carbon policy.
https://katalog.adlr.link/Record/ai-55-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9EQUVEX2FfMDAxNDY